Taxonomic notes on the genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) from Vietnam with key to all known species in the Oriental region - Lien, Nguyen Thi Phuong; Ngat, Tran Thi; Minh, Hoang Gia (Zootaxa, 2020)
There are two species of the genus Pseumenes Giordani Soika, 1935 occurring in Vietnam, Pseumenes depressus depressus (de Saussure, 1855) and a new species, Pseumenes fulvus Nguyen. The new species is described and figured. A key to all known species of this genus from the Oriental region is provided.